2020
DOI: 10.31234/osf.io/ydrm9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child, parent, and family mental health and functioning in Australia during COVID-19: Comparison to pre-pandemic data

Abstract: The COVID-19 pandemic presents significant risks to the mental health and wellbeing of families. This study aimed to examine: (1) patterns of parent and child (0–18 years) mental health, parent substance use, couple conflict, parenting practices, and family functioning during COVID-19 compared to pre-pandemic data; and (2) associations between parent, child, and family outcomes during the pandemic and both pre-existing risk factors and COVID-19 stressors. Participants were Australian mothers (81%) and fathers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 57 publications
2
66
1
4
Order By: Relevance
“…Another preprint study on families showed greater parental anxiety symptoms during the pandemic, compared to pre-pandemic data [12]. In this last study, pre-existing financial deprivation, parental chronic physical or mental health condition, and COVID-19 stressors (e.g., job loss, employment changes, illness, food shortages, housing or financial insecurity) were associated with greater parental anxiety symptoms [12]. Another study reported increased physical and mental health problems in parents and children between March and June 2020 [14].…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Another preprint study on families showed greater parental anxiety symptoms during the pandemic, compared to pre-pandemic data [12]. In this last study, pre-existing financial deprivation, parental chronic physical or mental health condition, and COVID-19 stressors (e.g., job loss, employment changes, illness, food shortages, housing or financial insecurity) were associated with greater parental anxiety symptoms [12]. Another study reported increased physical and mental health problems in parents and children between March and June 2020 [14].…”
Section: Introductionmentioning
confidence: 90%
“…Family studies have also found greater anxiety symptoms [15][16][17][18][19][20][21][22][23][24][25] worries and fears [15,19,26], acute stress and posttraumatic stress disorders [27], as well as sleep disturbances [19] in children, related to the outbreak and lockdown. Pre-existing financial deprivation [12,25], parental chronic physical or mental health condition [12], COVID-19 stressors (e.g., job loss, employment changes, illness, food shortages, housing or financial insecurity) [12] and having relatives infected with COVID-19 [25] were associated with higher child anxiety symptoms. Additionally, being a girl [17,23,24] has been associated with higher anxiety levels during the COVID-19 outbreak [15,20].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Among Swiss young adults, low parental monitoring was associated with lower COVID-19 protective behavior compliance [ 21 ]. However, family factors such as conflict and emotion expression were related with COVID-19 stressors [ 28 ]. Thus, it is of interest to determine how COVID-19 stressors affect such family factors, which thereby may influence protective behaviors against COVID-19 with the intention to reduce the spread of COVID-19 and associated stressors.…”
Section: Introductionmentioning
confidence: 99%